Lake Michigan Hydrodynamics: Mysis and Larval Fish Interactions - Wang, Yutta (UWM Digital Commons, 2013)
I studied the interactions between Lake Michigan hydrodynamics (the spring thermal bar) and Mysis, deepwater sculpin, and burbot larvae. The thermal bar is a zone of sinking 4º С water that separates warmer inshore water from colder offshore water. Mysis was a major bycatch of sampling for larval fishes. The density of Mysis did not differ statistically between inshore (about 6º С) and offshore of the thermal bar, but the percentage of Mysis that were newborns was significantly higher inshore (P = 0.007). These "early start" coastal Mysis may have an advantage in growth and survival, but with the risk that, unless they drift offshore, they will be at bottom depths that are ultimately inhospitable. The thermal bar period, and shortly thereafter, may be the only time that Mysis and the invasive Hemimysis anomala significantly overlap spatially. The most important impact of these newborn Mysis may be for newly free-swimming and free-feeding Age-0 lake trout (Salvelinus namaycush) which, for coastal reefs, emerge from spawning reefs during the period of thermal bar dynamics. The density of larval deepwater sculpin was higher inside of the thermal bar. For four out of nine sampling dates, inshore deepwater sculpin were significantly (p<0.05) larger. While the density of Liminocalanus copepods density did not differ between inside vs. outside of the thermal bar, the larvae inshore consumed significantly (p=< 0.038) more prey (Liminocalanus copepods). Subsequent analysis using daily growth rings suggested that inshore larvae had significantly (p< 0.05) higher daily growth rates than offshore larvae, which could result in larger body size and better ability of catching prey and avoiding predators. After the pelagic period, deepwater sculpin larvae need to go back offshore and become demersal. If inshore larvae can't return offshore and settle, they wouldn't contribute to the recruitment. However, from the perspective of growth, the deepwater sculpin larvae benefit from being inside of the thermal bar. Burbot ...